Geopolitical Risk, Sustainability and “Cross-Border Spillovers” in Emerging Markets, Volume II Constitutional Political Economy, Pandemics-Governance And Labor-Oriented Bail-outs/Bail-ins - Nwogugu, Michael I. C. (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
XXI, 580 p. 17 illus., 16 illus. in color.